Use of fishermen's local ecological knowledge to understand historic red tide severity patterns. (November 2022) - Blake, Suzana Dumitrita; McPherson, Matthew; Karnauskas, Mandy; Sagarese, Skyler Rose; Rios, Adyan; Stoltz, Amanda Daria; Mastitski, Anthony; Jepson, Michael
Abstract: In the past decade, the Florida Gulf Coast has experienced a number of severe outbreaks of Karenia brevis, a marine alga that produces harmful algal bloom (HAB) events commonly called "red tides." These recurring red tide events have produced severe ecological and economic impacts. Although satellite and water sampling information can be used to identify and track the movement of more recent red tide events, the historic patterns of red tide occurrence and severity are less known. In addition, relatively little information is available about the impact of different red tide events on fish populations, marine habitats and the fishing industry over time. This presents a challenge to fisheries managers in accounting for the impacts of red tides in fisheries stock assessments and formulating policies that anticipate and mitigate the impact of red tide events on fishing dependent businesses. This paper describes the application of fishermen's local ecological knowledge (LEK) data to improve the historic record on red tides on the west coast of Florida, and develop a red tide severity scale. In addition, this paper sheds light on the ecosystem-level insights that fishermen bring to the study of red tides. Eight years were consistently identified by interviewees, with some of the most severe red tide occurrences having increased in frequency in the last fifteen years. The paper concludes with a discussion on existing and possible future applications of the LEK data on red tides for fisheries assessment and management. Highlights: Fishermen observed that extreme red tide events have increased in frequency in the last fifteen years. Fishermen observed that extreme red tides contribute to habitat loss and long recovery rates of fish populations. The socio-economic impacts of red tide events are not uniform, with some fishermen facing severe impacts on their livelihoods, while other fishermen being able to adapt and mitigate the negative impacts to their businesses. Fishermen LEK broadens our understanding of the ecosystem-level impacts of red tides for both present and past red tide events.